Preparation of methylammonium lead iodide (CH3NH3PbI3) thin film perovskite solar cells by chemical vapor deposition using methylamine gas (CH3NH2) and hydrogen iodide gas. Issue 9 (22nd May 2020) - Mortan, Claudiu; Hellmann, Tim; Buchhorn, Moritz; d'Eril Melzi, Marco; Clemens, Oliver; Mayer, Thomas; Jaegermann, Wolfram
Abstract: An upscalable chemical vapor deposition setup has been built‐up and employed in producing methylammonium lead iodide (MAPI) thin film perovskite solar cells, leading to a maximum efficiency of 12.9%. The method makes use of methylamine gas and hydrogen iodide gas to transform a predeposited layer of lead(II)iodide (PbI2 ) into MAPI. Although the reaction mechanism includes the intermediate phases lead oxide (PbO) and lead hydroxide (Pb(OH)2 ), indicated at least on the surface of the samples by XPS, neither species could be observed in XRD measurements of the stepwise reaction, which show a mixture of highly oriented cubic and tetragonal MAPI perovskite lattice systems. Abstract : An upscalable chemical vapor deposition setup has been built‐up and employed in producing methylammonium lead iodide (MAPI) thin film perovskite solar cells, leading to a maximum efficiency of 12.9%. The method makes use of methylamine gas and hydrogen iodide gas to transform a predeposited layer of lead(II)iodide (PbI2) into MAPI.